Aetiology and Findings of Recurrent Chronic Rhino Sinusitis with Nasal Polyposis after Functional Endoscopic Sinus Surgery - Ali Aziz Abed1 , Ragheed Turky Miteab2 , Ali Majid2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Nasal polyps are the edematous sinonasal mucosa prolapsing into the nasal cavity. Allergy,asthma, aspirin intolerance and fungal rhinosinusitis have been implicated in various studies. Recurrenceof nasal polyposis after functional endoscopic sinus surgery is prevalent but there are no specific causes forrecurrence. Intensity of relapse varies depending on multiple factors that implicated in showing charactersand findings of the recurrence.Objective: To evaluate causes of nasal polyposis recurrence after FESS.Patients and method: 30 adult patients age between 18 and 60 years (with recurrent nasal polyposis afterFESS) were studied in the period between March 2017 and September 2018. Assessment done for allpatients by taking Medical history, documented data from the primary surgery, rhinoscopy with CT-scanexamination.Results: In this study, most of nasal polyp recurrence occur in 1-3 years after primary surgery, patients usingpost-operative steroid showed delay in recurrence, post-operative antibiotic showed no effect on time ofrecurrence,patients with (asthma, allergy, aspirin sensitivity and allergic fungal rhinosinusitis) showed highlund-kennedy and lund-mackay scores and some patients had anatomical findings mainly (40% incompleteanterior ethoidectomy).Conclusions: Recurrence of nasal polyposis could occur at any age mainly in middle age group and malegender showed higher prevalence. Asthma, aspirin sensitivity (Samter’s tried) and allergic fungal sinusitiswere the most important associated diseases. CT-scan showed some anatomical variations like incompleteanterior and posterior ethmoidectomy which occupying the highest percentages. Post-operative steroidshowed delay in time of recurrence.